2012
DOI: 10.1007/s00606-012-0601-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity analysis of Rhododendron aureum Georgi (Ericaceae) located on Changbai Mountain using ISSR and RAPD markers

Abstract: Rhododendron aureum Georgi (Ericaceae) is a perennial alpine shrub endemic to Changbai Mountain in China. We used ISSR and RAPD markers to describe the diversity and genetic structure within and among four natural populations located at different altitudes. DNA from 66 individuals was amplified with ten ISSR markers and seven RAPD markers. High genetic diversity was observed by these two techniques at the species level. The genetic diversity of populations increased with altitudinal gradients from low to high.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 48 publications
3
19
1
Order By: Relevance
“…Studies also show that genetic variations occurred along elevation gradients because topographical heterogeneity of plants habitat causes substantial changes in the environment (Byars et al 2009;Kumar et al 2014;Ohsawa and Ide 2008). It is also reported that at different altitudes strong isolation of populations may occur due to drastic differences in phenology between higher and lower altitudes and mountain barriers which restricts the gene flow between the populations causing complex and varied genetic variations (Arnaud-Haond et al 2006;Kumar et al 2014;Liu et al 2012). This is also supported by the present study where populations of the plain or sloppy belts of Garo hills exhibit low levels of genetic diversity and are distinct from the populations of the hilly terrain of Khasi, Jaintia and Ri Bhoi districts of Meghalaya, where diversity is higher.…”
Section: Discussionmentioning
confidence: 99%
“…Studies also show that genetic variations occurred along elevation gradients because topographical heterogeneity of plants habitat causes substantial changes in the environment (Byars et al 2009;Kumar et al 2014;Ohsawa and Ide 2008). It is also reported that at different altitudes strong isolation of populations may occur due to drastic differences in phenology between higher and lower altitudes and mountain barriers which restricts the gene flow between the populations causing complex and varied genetic variations (Arnaud-Haond et al 2006;Kumar et al 2014;Liu et al 2012). This is also supported by the present study where populations of the plain or sloppy belts of Garo hills exhibit low levels of genetic diversity and are distinct from the populations of the hilly terrain of Khasi, Jaintia and Ri Bhoi districts of Meghalaya, where diversity is higher.…”
Section: Discussionmentioning
confidence: 99%
“…ISSRs have been previously successfully used to study the genetic variation of species of conservation concern (e.g. George et al 2009;Liu et al 2012;Cires et al 2013;Xing et al 2015), including Pittosporum Banks ex Solander species (Carrodus 2009;Clarkson 2011;Mendes et al 2011;Clarkson et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Species of the genus Rhododendron, one of the most valuable and largest genera of woody plants, are dominant shrubs with frequently narrow distribution in their natural habitats, whose current conservation status need attention (Li et al 2015). However, there are only a few studies of genetic diversity in Rhododendron species carried out with microsatellite markers (Liu et al 2012, Song et al 2012, Sharma et al 2014, Wu et al 2014b, Wang et al 2016. In general, widespread and long-lived plant species tend to possess high levels of genetic diversity, with H E ranging from 0.3 to 0.8 (Takezaki andNei 1996, Wang et al 2013a).…”
Section: Discussionmentioning
confidence: 99%